2021
DOI: 10.1016/j.jhepr.2020.100190
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection for hepatocellular carcinoma in patients with clinically significant portal hypertension

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…A recent multicentric study showed that cirrhotic patients with a hepatic venous pressure gradient of ten or more could undergo liver resection with an acceptable 90-day perioperative mortality and morbidity (6% and 27%, respectively) and persistent liver decompensation (10% at 3 months) (7). In many Asian studies, the extent of surgery was applied where technically feasible, including in patients with macrovascular invasion (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent multicentric study showed that cirrhotic patients with a hepatic venous pressure gradient of ten or more could undergo liver resection with an acceptable 90-day perioperative mortality and morbidity (6% and 27%, respectively) and persistent liver decompensation (10% at 3 months) (7). In many Asian studies, the extent of surgery was applied where technically feasible, including in patients with macrovascular invasion (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Resection is recommended for those at BCLC stage 0 or BCLC-A with a solitary nodule (4,5). Additionally, the patient must be an optimal candidate meeting the following criteria: compensated Child-Pugh class A liver function, model for endstage liver disease (MELD) score of <10, and matched grade portal hypertension (4,6,7). In Asia, the classification system is designed to detect HCC earlier with higher sensitivity and lower specificity (8).…”
Section: Introductionmentioning
confidence: 99%
“…According to this hierarchical interaction (portal pressure + extent of resection + MELD score), HVPG > 10 mmHg or indirect evidence of CSPH are no longer an absolute contraindication for HCC resection in patients with cirrhosis, if MELD is below 10 and the resection limited. Other studies which included patients with HVPG > 10 mmHg found an acceptable risk of PHLF of about 5-30%, with an acceptable 36-month survival (about 75%) [19]. In the case of HVPG > 10 mmHg, we should select those with a good performance status (PS 0-1), with preserved liver function (MELD <10), and without any sign of clinical decompensation of liver cirrhosis (only Child A5-6), including the absence of esophageal varices.…”
Section: Predictors Of Post-hepatectomy Liver Failurementioning
confidence: 94%
“…With the development of artificial intelligence and information, deep convolutional neural network has been used in the segmentation of medical images, and its performance is far superior to traditional machine learning algorithms [11,12]. Souhami et al [13] proposed a 3D deep full convolutional neural network (FCNN) architecture to segment the lesions in MRI images of the prostate gland by combining the characteristics of the lesions and the information of its surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%